Current land use and hydrogeomorphological quality of the San Antonio River: alternatives for the ﬂuvial restoration in northern Peru - Rolando Salas, Elgar Barboza (2018)
The objective of the study was to evaluate the current land use and hydrogeomorphological quality in the San Antonio River, located between the provinces of Chachapoyas and Rodríguez de Mendoza in the Department of Amazonas (Peru). The land uses were estimated using the supervised classification method for the Sentinel 2A images, while the assessment of the quality of the fluvial system was carried out through the application of the hydrogeomorphological index (IHG) in each functional sector. The results reported that the soil cover in the San Antonio microbasin is managed in the following way: 44.50% occupied by crops, 36.09% by forests, 11.24% by pasture, 7.56% by grassland and shrubs, and 0.61% is an urban area and water bodies. In turn, the hydrogeomorphological quality of the San Antonio River is in a range of quality from Very Good to Deficient, with a greater anthropic impact in the middle and lower sections of the river. It is concluded that the use of soil influences hydrogeomorphological quality due to agricultural activities, urban use and extraction of construction materials in the riverbed, which contributes to the degradation of the fluvial system.